OLIVINE-CLINOPYROXENE PARAGENESIS OF THE PHENOCRYSTS IN CLINOPYROXENITE OF THE SOUTHERN URALS - Pushkarev Ye.V. (My University, 1989)
The finding of porphyritic phenocrysts of rock-forming materials in completely crystallized ultramafic rocks is uncommon, and each such find is therefore of considerable interest. Olivine and clinopyroxene phenocrysts were found in olivine-containing clinopyroxenite of the Molostovskiy complex. The clinopyroxenite is the earliest rock of the differentiated clinopyroxenite-gabbro-granite series, which is found untruncated in ring intrusions intersecting the harzburgite of the Khabarninskiy pluton in the southern Urals. Without going into the geology of these structures or the composition of their rocks, the author briefly describes the ultramafic rocks. These consist of completely crystalline moderately to coarse-grained olivine-containing clinopyroxenite of dark greenish-black color. The rocks consist of olivine (10 to 12 percent) and clinopyroxene (65 to 70 percent), forming euhedral crystals cemented by xenomorphic later hornblende. The rocks have a poikilitic texture.